Hybrid Bio-Ceramic Composites for High Temperature Protection in Aerospace and Defense Systems - Sovian Aritonang (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Purpose – This article aims to develop an integrative framework for utilizing hybrid bio-ceramic composites as high-temperature protective materials in aerospace and defense systems. The focus is on enhancing the extreme heat resistance of bio-ceramics through hybridization with metals or polymers to create durable materials capable of withstanding hypersonic conditions and extreme aerothermal environments. Design/Methodology/Approach – This study uses the Systematic Literature Review (SLR) method, analyzing scientific publications indexed by Scopus, Web of Science, and SINTA from 2015 to 2025. The review explores the development of bio-ceramic composite research, hybridization strategies with polymers and lightweight metals, and manufacturing innovations that enhance material performance in thermal protection systems for aerospace applications. Findings – The literature review shows that hybrid bio-ceramic composites outperform conventional materials. These composites can endure temperatures up to 1800 °C, possess high resistance to oxidation, ablation, and thermal shock, and are lightweight for aeronautical use. Biomimetic designs inspired by mollusk shells and bones improve fracture toughness and mechanical performance. Hybridization with polymers and lightweight metals expands the potential applications in hypersonic aircraft and modern defense systems. Practical Implications – The findings are crucial for developing jet engine shields, hypersonic missiles, and space re-entry capsules. For Indonesia, this research offers opportunities to reduce reliance on imported high-temperature materials and enhance national defense industry independence. Originality/Value – The article contributes a new perspective by highlighting bio-ceramic hybrids as strategic materials capable of withstanding extreme temperatures, integrating biomimetic principles and composite technology for modern defense systems.